(untitled) (Oxford, 1995)
This workbook presents worked examples and set problems that cover one- and two-dimensional NMR techniques as applied to organic and inorganic systems. Most of the problems are genuine research examples, and this second edition contains numerous new problems derived from recent work, particularly with regard to symmetry and exchange. This new edition is fully compatible with the second edition of Modern NMR Spectroscopy: A Guide for Chemists
Keywords: Nuclear magnetic resonance spectroscopy,Phổ học cộng hưởng từ hạt nhân; Problems, exercises, etc.,Câu hỏi và bài tập, v.v